Orientin and vitexin attenuate lipopolysaccharide-induced inflammatory responses in RAW264.7 cells: a molecular docking study, biochemical characterization, and mechanism analysis - Yue Yu; Fusheng Pei; Zhanming Li (Food Science and Human Wellness, 2022)
ABSTRACT: Plant flavonoids have received considerable attention for their health benefits. However, structure-activity relationships between flavonoids such as orientin and vitexin with similar structures are rarely reported. In the present study, molecular docking study suggested that orientin and vitexin suppressed inflammatory responses through the modulation of the mitogen-activated protein kinase (MAPK) signaling pathway. Moreover, RAW264.7 cells with lipopolysaccharide-induced inflammation were used to evaluate the anti-inflammatory activities of orientin and vitexin, based on the inflammation-related cytokines production, quantitative real-time reverse transcription PCR, and western blotting analysis. As a result, orientin or vitexin attenuated inflammatory responses through modulation of the MAPK/NF-κB signaling pathway by suppressing NF-κB translocation.